1996
DOI: 10.1007/bf01983600
|View full text |Cite
|
Sign up to set email alerts
|

Thermal analysis of poly(2-methylpentamethylene terephthalamide)

Abstract: Poly(2-methylpentamethylene terephthalamide) (Nylon M5T) is a new high temperature aromatic polyamide developed by Hoechst Celanese. In this paper thermal properties of Nylon M5T chips, as well as as-spun and drawn fibers were studied by DSC, DMA, hot stage microscopy and WAXS. Tg of the fully amorphous Nylon M5T is 143~ when measured by DSC; T~ increases with crystallinity to 151~ The temperature dependence of the solid and melt specific heat capacities has also been determined. The heat capacity increase at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…This molecule is shown in Formula 10. Menczel et al [133] prepared polyamide from 2-MPMD and TPA: they found the polymer slow to crystallize on solidification and to possess three different crystal forms. Villasenor et al [134] prepared polymers of 2-MPMD with adipic acid (six carbons) and sebacic acid (ten carbons) and they observed quite different crystal structures from the simple polyamides 56 and 510 which also have a 5-carbon linear diamine chain.…”
Section: Polyamides From Monomers With Side Substituentsmentioning
confidence: 99%
“…This molecule is shown in Formula 10. Menczel et al [133] prepared polyamide from 2-MPMD and TPA: they found the polymer slow to crystallize on solidification and to possess three different crystal forms. Villasenor et al [134] prepared polymers of 2-MPMD with adipic acid (six carbons) and sebacic acid (ten carbons) and they observed quite different crystal structures from the simple polyamides 56 and 510 which also have a 5-carbon linear diamine chain.…”
Section: Polyamides From Monomers With Side Substituentsmentioning
confidence: 99%